Altered regional homogeneity in delayed encephalopathy after carbon monoxide poisoning: A resting-state fMRI study. (11th June 2020) - Wu, Kaifu; Liu, Meng; Zhao, Guoshu; He, Laichang; Tan, Yongming
Highlights: The new study investigated spontaneous brain activity in DEACMP via fMRI. Negative correlation was found between MMSE and ReHo in posterior cingulate gyrus. These findings provided evidence for local brain dysfunctions and may help understand the neuropathologic mechanism for DEACMP. Abstract: Objective: To investigate alternations in spontaneous brain activities reflected by regional homogeneity (ReHo) in patients with delayed encephalopathy after acute carbon monoxide poisoning (DEACMP) using resting-state functional magnetic resonance imaging (rs-fMRI). Methods: Twenty-one patients with DEACMP and 21 age, sex and education matched healthy controls (HCs) received rs-fMRI scanning and clinical assessment. We used the ReHo method to analyze the interregional synchronized activity of all participants. Two sample t-tests were performed to compare the ReHo maps between the two groups. Pearson correlation analysis was then used to assess the correlations between clinical measures and abnormal ReHo in DEACMP patients. Results: Compared with HCs, DEACMP patients showed significantly decreased ReHo in bilateral cerebellum posterior lobe, pons, bilateral basal ganglia, while increased in the posterior cingulate, calcarine, bilateral occipital lobe(GRF correction, voxel P value <0.001, cluster P value <0.05). Negative correlation was found between Mini-mental State Examination (MMSE) scores and the ReHo values of posterior cingulate gyrus (r = −0.672, p < 0.05) in the DEACMP group, while positively related to the time from CO poisoning to MRI scan (r = 0.428, p < 0.05). Conclusion: Patients with DEACMP exhibited altered ReHo in the multiple functional brain regions, which provide evidence for local brain dysfunctions and may help to understand the neuropathologic mechanism for the disease.